Risk factors for type 2 diabetes mellitus in rural communities in South Sumatra, Indonesia - Sari, Yoki Arum; Najmah, Najmah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood sugar levels caused by insulin resistance or impaired insulin secretion. The prevalence of type 2 diabetes mellitus continues to increase, especially in rural areas due to low public awareness and limited access to non-communicable disease control. Method: To case-control design involving patients undergoing outpatient treatment at the Indralaya Community Health Center. The study sample consisted of 143 cases and 143 controls. Sampling in the control group was performed using a “non-matching” technique. Data were collected through questionnaires and medical record analysis. Results: Data analysis used the Chi Square test with a 95% confidence level. Of the 143 respondents, 143 were found to have diabetes mellitus. The results of the analysis showed a significant relationship between gender, income, family history of DM, diet, physical activity, and blood pressure on the incidence of type 2 DM in the Indralaya Community Health Center area after controlling for the IMT variable. Meanwhile, age, occupation, education, and smoking were confounding variables and did not have a significant relationship with the incidence of type 2 DM. The dominant variables associated with the incidence of type 2 DM were income and family history of DM. Conclusion: Income and family history of DM are the most dominant determinants causing type 2 DM in rural areas. Gender, diet, physical activity, and blood pressure are also associated with the incidence of type 2 DM in the Indralaya Community Health Center area after controlling for the BMI variable. The dissemination of information and education is very important for health workers to provide to high-risk communities in order to prevent this disease.